HUBUNGAN KELENTUKAN OTOT PUNGGUNG DAN EXPLOSIVE POWER OTOT LENGAN DAN BAHU DENGAN HASIL LEMPAR CAKRAM PADA MAHASISWA PUTRA 4B PENJASKESREK ANGKATAN 2012 UNIVERSITAS RIAU - Rispika Sandra Sandra; Slamet '; Zainur ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: The problem in this study originated from the observation that the authors found in the field, the results of men's discus throw 4B students penjaskesrek 2012 University of Riau has yet to get the maximum throw. The purpose of this study was to determine the relationship of back muscle flexibility and explosive power arm and shoulder muscles with the results of men's discus throw at the 2012 University of Riau penjaskesrek 4B.The population in this study was student son 4B penjaskesrek 2012 University of Riau, amounting to 34 people using the technique of total side where all the population sampled, to obtain research data used to test the flexibility of the back muscles crunches and recth, Two-Hand Medicine Ball Put and results discus throw. Data were analyzed by simple and multiple product moment.Based on the analysis of the data found that the results obtained flexibility of the back muscles have a relationship with the results of men's discus throw at the students 4B penjaskesrek 2012 University of Riau. From the results obtained explosive power arm and shoulder muscles have relations with the result mahassiwa men's discus throw at the 2012 University of Riau penjaskesrek 4B. There is a relationship together between back muscle flexibility and explosive power arm and shoulder muscles with the results of student men's discus throw at the 2012 University of Riau penjaskesrek 4B. Keywords: back muscle flexibility, Explosive Muscle Power Arm And Shoulder, Discus Throw Results